2011 - 2013 cycle of the TrainForTrade port training programme : English-speaking network (UN New YorkUS, 2014)
Presents the dissertations from the past cycle of the English-speaking network of the Train-For-Trade Port Training Programme (2011-2013). Gives background information on the programme, in particular the English-speaking network, and explains the dissertation process. Focuses on the results of the research done by the participants and provides summaries of the best three dissertations from each member country: Ghana, Indonesia, the Maldives, Namibia and the United Republic of Tanzania.
Keywords: PORTS